Tennis performance in relation to VO2max: A case report - Thiel, C.; Banzer, W.; Rosenhagen, A.; Vogt, L. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In professional tennis, the preparation period at the end of the year offers the best possibility to systematically develop athletic capabilities. Improving the aerobic capacity in this period may be relevant for tennis performance. The present case study examined the relationship between VO2max during preparation and next year`s entry ranking. Methods: The athlete (180 cm, 74kg) plays a defensive baseline game, prefers hardcourts and shows excellent speed and agility capabilities and average aerobic capacity. Breath-by-breath detection of ventilation and beat-to-beat heart rate were assessed using the same maximal graded exercise protocol on a calibrated treadmill ergometer and an Oxyon mobile spirometer over 7 successive years. VO2max was obtained from the last 30 seconds of the final stage, applying standard VO2max criteria. Ranking was obtained from the official year-end ATP tour entry ranking list. Results: From 1999 to 2006, the athlete reached a VO2max between 55.0 and 67.4 mL/min/kg and ATP ranking positions between 6 and 97. Cross-correlation analysis indicated a strong relationship between VO2max and ATP entry ranking over time (r=-0.938, p<.001, lag 1). Discussion: On the basis of the current results, the individual respiratory capacity may explain up to over 80% of an individual athlete`s ranking position in the following year. Discrepancies between VO2max and the ranking, as seen in 2006, may be attributed to an illness-caused training reduction of several months. These findings emphasize the relevance of continuous performance tests to improve the effectiveness of the preseason training period, and to optimise the athletic capabilities of high-class tennis players.